Polarization-insensitive multimode interference coupler based on bricked subwavelength gratings - Pérez-Armenta, Carlos; Ortega-Moñux, Alejandro; Luque-González, José Manuel; Halir, Robert; Reyes Iglesias, Pedro José; Schmid, Jens H.; Cheben, Pavel; Molina-Fernández, Íñigo; Wanguemert-Pérez, Juan Gonzalo (My University, 2022)
The recently proposed bricked patterning enables enhanced performance in integrated photonics devices based on subwavelength gratings, including polarization insensitivity. We report on the design of a polarization-agnostic 2×2 multimode interference coupler for the 220 nm silicon-on-insulator platform using the bricked SWG metamaterial, operating in telecom O-band.
Keywords: Comunicaciones; Fotones; Interferómetros de polarización; Metamateriales; Subwavelength gratings; On-chip metamaterials; Multimode interference; Polarization insensitivity; Silicon-on-insulator